Study on Mechanism of Structure Angle on Microstructure and Properties of SLM-Fabricated 316L Stainless Steel - Li, Xiaofeng; Yi, Denghao; Wu, Xiaoyu; Zhang, Jinfang; Yang, Xiaohui; Zhao, Zixuan; Wang, Jianhong; Liu, Bin; Bai, Peikang (Frontiers in Bioengineering and Biotechnology, 2021)
In this study, seven 316L stainless steel (316L SS) bulks with different angles (0°, 15°, 30°, 45°, 60°, 75°, and 90°) relative to a build substrate were built via selective laser melting (SLM). The influences of different angles on the metallography, microstructure evolution, tensile properties, and corrosion resistance of 316L SS were studied. The 0° sample showed the morphology of corrugated columnar grains, while the 90° sample exhibited equiaxed grains but with a strong <101> texture. The 60° sample had a good strength and plasticity: the tensile strength with 708 MPa, the yield strength with 588 MPa, and the elongation with 54.51%. The dislocation strengthening and grain refinement play a vital role in the mechanical properties for different anisotropy of the SLM-fabricated 316L SS. The 90° sample had greater toughness and corrosion resistance, owing to the higher volume fraction of low-angle grain boundaries and finer grains.